1998
DOI: 10.1002/(sici)1098-2744(199802)21:2<81::aid-mc1>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Amplification and overexpression of theAKT2 oncogene in a subset of human pancreatic ductal adenocarcinomas

Abstract: AKT2, an oncogene encoding a protein serine-threonine kinase implicated in phosphatidylinositol-3-OH kinase signaling, is amplified in some human ovarian and pancreatic carcinomas. We previously demonstrated that the tumorigenicity and invasiveness of pancreatic ductal adenocarcinoma (PDAC) cell lines with amplified AKT2 could be markedly reduced by transfection with antisense AKT2 constructs. To evaluate further the extent of AKT2 alterations in PDAC, DNA and immunohistochemical analyses were performed to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 284 publications
(61 citation statements)
references
References 21 publications
1
58
0
Order By: Relevance
“…We suggest that activation of AKT2 in particular plays an important role in breast tumorigenesis based on the immunohistochemical analyses showing overexpression of AKT2 in the breast tumors. The cytoplasmic staining of phospho-AKT in tumors also is similar to previous reports (Sun et al, 2001a,b), and overlaps with the staining for AKT2 expression using both polyclonal AKT2 antibodies and a monoclonal AKT2 antibody previously used for the analysis of pancreatic tumors (Ruggeri et al, 1998). Because the phospho-speci®c, pan-AKT antibodies recognize equivalent phosphorylation sites in AKT1, AKT2 and AKT3, we acknowledge that our positively-stained para n-embedded tumor specimens may have activation of multiple AKT isoforms.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We suggest that activation of AKT2 in particular plays an important role in breast tumorigenesis based on the immunohistochemical analyses showing overexpression of AKT2 in the breast tumors. The cytoplasmic staining of phospho-AKT in tumors also is similar to previous reports (Sun et al, 2001a,b), and overlaps with the staining for AKT2 expression using both polyclonal AKT2 antibodies and a monoclonal AKT2 antibody previously used for the analysis of pancreatic tumors (Ruggeri et al, 1998). Because the phospho-speci®c, pan-AKT antibodies recognize equivalent phosphorylation sites in AKT1, AKT2 and AKT3, we acknowledge that our positively-stained para n-embedded tumor specimens may have activation of multiple AKT isoforms.…”
Section: Discussionsupporting
confidence: 88%
“…We have reported ampli®cation and overexpression of AKT2 in pancreatic and ovarian cancers (Bellacosa et al, 1995;Cheng et al, 1996;Ruggeri et al, 1998). In breast tumors, AKT3 over-expression has been reported in estrogen receptornegative breast tumors (Nakatani et al, 1999), and AKT1 activation has been reported in *40% of breast carcinomas (Sun et al, 2001a).…”
Section: Introductionmentioning
confidence: 79%
“…Mutation of p53 or elevation of antiapoptotic members of the Bcl-2 family are paradigms in cancer. As outlined above, activation of AKT by various means in cancer cells is also likely to be important (Franke et al, 1997;Frisch and Ruoslahti, 1997;Ruggeri et al, 1998;Wu et al, 1998). However, the executioner machinery remains intact in cells transformed by c-Myc, which may o er an Achilles' heel to exploit.…”
Section: Apoptosis: Its Signi®cance In Cancermentioning
confidence: 99%
“…For both Akt2 and Akt3 there are data suggesting a role in human cancer. Akt2 is ampli®ed and overexpressed in ovarian cancer, breast cancer and pancreatic cancer and Akt3 is overexpressed in breast and prostate cancer (Bellacosa et al, 1995;Cheng et al, 1992Cheng et al, , 1996Miwa et al, 1996;Nakatani et al, 1999b;Ruggeri et al, 1998). In this communication, we describe oncogenic transformation by Akt2 and Akt3 in experimental systems.…”
mentioning
confidence: 93%